Optimising the Main Function of Navy Materiel Development to Improve Operation Logistics in the National Capital, East Kalimantan - Saputra, Ditto Regina; Hidayat, Heru Syamsul; Yuana, Sunu Tri (Journal of Industrial Engineering & Management Research, 2024)
The relocation of the Capital City to East Kalimantan has become a government priority. This government policy is then outlined in Law Number 3 of 2022. The relocation of the Capital City to East Kalimantan should not only focus on economic aspects but also consider social, environmental, geopolitical, and especially defence aspects. The capital city will become the Military Command Headquarters, which is expected to be able to react to enemy forces when moving into the outer region, as well as become a control centre in dealing with contingency situations. As a sea defence force, the Indonesian Navy is tasked with maintaining the defence and security of Indonesia's sea territory, especially those around the capital city location in East Kalimantan. The defence and security tasks are carried out through operation titles that require operation logistics support. Operational logistics support cannot be separated from the role of material development, which is an effort and activity in preparing and providing integrated material needed to support capacity-building and the use of force. Navy materiel development has main functions, including determining needs, research and development, procurement, distribution and maintenance. However, in its implementation, the Navy's material development still needs to improve, including the following: First, Alutsista's needs must be entirely determined by the proposed needs plan. Second, the Navy's strategic defence equipment procurement relies heavily on foreign manufacturers. Third, the maintenance and repair capabilities of the Navy Base to support the operating elements (KRI and Pesud) still need to be optimal. For the primary function of the Navy's material development to be optimal to improve logistics operations in the National Capital, the existing problems must be resolved appropriately and quickly. Problem-solving of existing problems includes: First, determining defence equipment needs must be based on a needs plan. They were second, increasing the role of the domestic Defence Industry (Indhan) to produce the Navy's strategic defence equipment to achieve self-reliance. Third, they improved the capabilities and infrastructure of the Navy's base facilities to support maintaining and repairing elements in the operating area. Problem-solving is elaborated on through the efforts of regulation, procurement, coordination, cooperation, and evaluation.